Gunship Over Angola : The Story of a Maverick Pilot - Delport, Anri (Scientia Militaria - South African Journal of Military Studies, 2021)
“Most war stories”, according to Hynes, “begin with a nobody-in-particularyoung man, who lives through the experience of war, to emerge at the end definedby what has happened to him.”443 One such “nobody-in-particular young man” wasnational serviceman 74257684BC Private Stephen Pierre Joubert, born on 3 July 1958in Chingola, then Northern Rhodesia.444 Since the age of five, he and his family livedin Pretoria. He had a typical childhood in most respects.445 Barely seventeen yearsold, he, like many other young men, reported for national service. One year later,in 1977, he stood in a “perfectly pressed” uniform with “buttons and badges [that]sparkled like diamonds” in a large room in a nondescript building at the South AfricanAirforce (SAAF) Gymnasium in Valhalla, Pretoria.446 Facing him was an intimidating,expressionless collection of brass seated in a semicircle. It was Joubert’s second PilotSelection Board interview for the Pupil Pilot’s Course. Among the brass was thelegendary aviator, World War II and Korean War veteran, then chief of the SAAF,General Bob Rogers. The general asked the first question, “[h]ow long have you wantedto be a pilot?” Joubert responded, “[s]ince I stopped wanting to be an ice cream seller,sir!”447 Two years later, “on an early November day”, 21-year-old Joubert with wingspinned to his chest stepped onto AFB Ondangwa in South West Africa, now calledNamibia.448 The events that followed changed him forever. It was as Hynes notes, “outof that nobody, war has forged a self”.